Overseas Direct Investments to the Wholly Owned Subsidiaries and Their Association with Indian Macroeconomic Factors - Vijayalakshmi, D.; Menon, Shalini K. (Indian Journal of Finance, 2023)
Purpose : The present study focused on analyzing the macroeconomic factors of the home country (India) before investing in a wholly owned subsidiary (WOS) established in a foreign country. When an investment is made in a WOS, the entity must focus on several factors that would ensure profitability in the long run. Methodology : The overseas investments to the WOS are made through equity, loan, and guarantee or a combination of the same. The study considered the total overseas direct investments to the WOSs. The performance of the total overseas investments was analyzed using descriptive statistics. The short-run and long-run associations between the total overseas direct investment and the macroeconomic factors of the home country were estimated by employing the Granger causality test and Johansen cointegration test. Findings : The results proved the existence of a short-run association between select macroeconomic factors and overseas investments. A long-run association also existed between the variables. Practical Implications : Apart from firm-specific factors, several macroeconomic factors should also be considered before investing. In this context, the study focused on the performance of the ODI from India to the WOS in particular and the home country’s macroeconomic factors that should be evaluated before investing in a foreign country. Originality : Although several research studies were conducted on the performance and growth of overseas direct investments, studies about investments to the WOSs established abroad is a new research dimension in the area of overseas direct investments in the Indian scenario.